KOMUNIKASI KRIMINAL SUATU KEBUTUHAN KHUSUS SEBAGAI BIDANG KAJIAN BARU - Achmad, Ardan (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2010)
World was shocked by the October 12, 2001 bombing of terrorist to the world trade center of New York of the United States of America the date in which could be considered as the beginning of intense war of world news on terrorism. Analyses made about the responsible actors, motives for the tragic bombing are all political in character, almost forgetting that the act of bombing basically is a criminal act. Political actors are more intensively interviewed for the analyses than criminologist or lawyers or other relevant experts which ironically the other experts s comments but political actors s are used as a mere supportive political justification, such a politicalccommunication was and has intensively been applied in the situation. The concern rises why the criminal act is analysed/or the first place by its political character not by its criminal character? The political terminologies or concepts are pronounced where criminal concepts are marginalized er are probably not available to use and must be used in relation to the political concepts? So why do not we blend the concepts together to have a new formula of criminal communication? where we can come with the construction of criminal communication with its political dimension, not political communication with its criminal dimension. The first firstly puts an act of crime, and followed by its political character, whereas the second comes with its political character followed by its criminal dimension.